2018
DOI: 10.1021/acssuschemeng.8b00381
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Fano Resonance of Multishaped Cu2O Nanoparticles on ZnO Nanowires Modulating Efficiency of Hydrogen Generation in Water Splitting Cell

Abstract: The different-shape Cu2O nanostructured in solar water splitting system serves as the photon absorber structure for modulating photoelectric conversion to challenge the issue of the high resistance and low electronic mobility with the different light trapping effect due to the orientation and geometry of Cu2O. Finite difference time domain (FDTD) simulation results demonstrate that the Cu2O nanostructured of truncated octahedral exhibits photonic Fano resonance compared with the other shapes. The generation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Many configurations and shapes of metal nanoparticles have been fabricated and studied in photocatalysis. [193,[202][203][204][205] Many factors contribute to photocatalytic performance enhancement, including the formation of local electric field, light absorption enhancement due to SPR, and charge carriers generation improvement. [28] In 2018, Jeong et al demonstrated silver nanoparticles embedded in BiVO 4 nanocomposite photoanode to enhance photocatalytic current densities, as shown in Figure 13a.…”
Section: Plasmonic Resonancementioning
confidence: 99%
“…Many configurations and shapes of metal nanoparticles have been fabricated and studied in photocatalysis. [193,[202][203][204][205] Many factors contribute to photocatalytic performance enhancement, including the formation of local electric field, light absorption enhancement due to SPR, and charge carriers generation improvement. [28] In 2018, Jeong et al demonstrated silver nanoparticles embedded in BiVO 4 nanocomposite photoanode to enhance photocatalytic current densities, as shown in Figure 13a.…”
Section: Plasmonic Resonancementioning
confidence: 99%
“…The Cu 2 O as a p‐type semiconductor was focused on by scientists 22 . It has a wide application in solar cells 23 and photocatalytic hydrogen evolution 24,25 . One reason for choosing CoAl‐LDH was that it had an appropriate band structure that can form a p‐n heterojunction with the Cu 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The surface plasmon resonance induced hot electrons on the surface with noble metal nanostructures, and the semiconductor could transfer comparable energy, enabling water splitting for the generation of hydrogen. The tuning spectra of light trapping by SPR include the ultraviolet–visible light–near infrared regime. The spincurrent is able to be generated across the system interface when the applied gold NPs satisfy the conditions of SPR. This SPR integrates with optical spintronics, bridging the gap of SPR spintronics.…”
Section: Introductionmentioning
confidence: 99%